Prototype Sistem Anti Kriminal Menggunakan Open CV Pada Python Berbasis Mikrokontroller - -, sukarno; amar, Ishak; Mariki, I Wayan Wawan (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2025)
Security is the most important and primary thing in human life. It is generally known that security systems in the form of CCTV cameras and security guards have not been effective in providing a deterrent effect to criminals in carrying out their actions. So it takes a way to deal with this, the author created a prototype of an anti-crime security system using open CV on python based on a microcontroller. From the test results after conducting several experimental scenarios on the prototype that was created, it can function normally. The system created is able to identify or recognize facial samples at a distance of about 1.5 meters, with a minimum light intensity of 407 lux. The prototype is able to track the presence of target movements and can follow target movements from an angle of 0o-180o vertically and from an angle of 00-60o vertically, and can shoot targets in a stationary position within 5 seconds.